Influence of environmental parameters on atmospheric aerosol size distributions in a South African coastal zone - February, Faith (Department of Oceanography, 2024)
Aerosols are microscopic solid or liquid particles suspended in the atmosphere, which impact and are impacted by many physicochemical processes related to climate. By scattering and absorbing solar radiation and acting as cloud condensation nuclei, they have both a direct effect and indirect effect on Earth's radiative budget. The Intergovernmental Panel on Climate Change (IPCC) recognizes aerosols as an important component of climate change, and as such the estimation of their impacts on climate remains an important scientific challenge. Atmospheric aerosol sources include natural and anthropogenic emissions, and these are both present in coastal areas. Marine aerosols are a major contributor to total aerosols in coastal regions, and these aerosols can interact with other gases and molecules, and influence biogeochemical cycles, air quality, and human health. Due to the complex nature of aerosols in coastal areas and the importance of aerosols to climate change, there is a need for in-situ observational aerosol data from data poor regions, which is the case for most of the Southern Hemisphere. To that aim, this thesis presents an extensive series of measurements of aerosol properties (concentrations, sizes, and types) at the coastal location of Simon's Town in False Bay, to characterize these properties for the first time in a coastal region of South Africa. The study site provides the opportunity to measure these aerosol properties in pristine marine conditions exclusively, as well as mixed conditions typical of a coastal site. With these geographical advantages and long-term, unbiased measurements, the aerosol processes of generation, transport, dispersion, mixing, and deposition have been investigated under unique natural conditions. The data analyses focus on evaluating changes in the average particle size distributions with changes in meteorological parameters. An increase in aerosol concentrations with an increase in wind speed during clean marine conditions resulted in the identification of sea spray generation and long-range transport as the dominant natural aerosol processes with the type of aerosol being predominantly marine. For the NW conditions, a decrease in aerosol concentrations with an increase in wind speed led to the identification of dispersion as the dominant process. A mixture of aerosol types emerged, but the higher aerosol concentrations for the pure continental conditions compared to the pure marine conditions indicated that non-marine aerosols dominate around 0.4 μm and 10 μm. The main conclusions of this thesis focus on the behavior of natural sea spray aerosols in the absence of continental or anthropogenic sources. This highlights the pure marine influence of the Southern Ocean at this location and the unique opportunity to explore understudied natural aerosol processes absent from anthropogenic influence.